Analyses and Calculation of Steel Scrap Melting in a Multifunctional Hot Metal Ladle. Issue 3 (6th December 2018) - Deng, Shuai; Xu, Anjun; Yang, Guang; Wang, Hongbing
Abstract : To improve the utilization of steel scrap in the steel production process, the authors analyze the feasibility of adding scrap steel into the multifunctional ladle before hot metal tapping. Firstly, the authors provide an overview of the process. Secondly, theoretically study the melting process of scrap steel in the ladle along with the scrap steel melting mechanism is done. Finally, the effects of the addition of different types of scrap steel pretreated at various temperatures are examined using numerical calculation and simulation. The preheating temperature and specific surface area of the scrap steel had important effects on scrap steel melting. For the scrap steel with a specific surface area of 1.6 m 2 t −1, the melting rate decreased by 4 min t −1 as the preheating temperature was increased from 300 °C to 800 °C. For a preheating temperature of 800 °C, the melting rate increased by 4.5 min t −1 as the specific surface area increased from 3.3 to 26.1 m 2 t −1 . Another 2.2%–6% of scrap steel can be added under certain conditions. This approach provides an effective solution to the problem of melting large amounts of scrap steel in steel works, further increases the utilization of scrap steel during steel production, and reduces the cost of steel production. Abstract : In this paper, a scheme of adding scrap steel to the multifunctional ladle before hot metal tapping is proposed. The effects of the addition of different types of scrap steel pretreated at various temperatures are examined using numerical calculation and simulation. The scheme and numerical analysis results can be valuable references for practical engineering application.